2019
DOI: 10.1038/s41598-019-42521-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient removal and microalgal biomass production from different anaerobic digestion effluents with Chlorella species

Abstract: Potential of microalgal cultivation as an alternative approach to the treatment of anaerobic digestion (AD) effluents was examined using two representative Chlorella species, Chlorella vulgaris (CV) and Chlorella protothecoides (CP). Both species effectively removed NH 4 + -N from the AD effluents from four digesters treating different wastes under different operating conditions. In all experimental culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…The IR spectra of polluted water treated biomass represented an unstable of the peaks at 698 cm -1 and 690 cm -1 . Similarly, Yu et al (2019) reported the FTIR transmittance of dried biomass of Scenedesmus sp. as an aliphatic character at 400-800, phenols, and alcoholic groups at 1,000-1,400, carboxyl group at 1,500-1,700 cm -1 , hydroxyl group: 3,200-3,400 cm -1 .…”
Section: Ftir and Sem Analysis Of Scenedesmus Spmentioning
confidence: 94%
“…The IR spectra of polluted water treated biomass represented an unstable of the peaks at 698 cm -1 and 690 cm -1 . Similarly, Yu et al (2019) reported the FTIR transmittance of dried biomass of Scenedesmus sp. as an aliphatic character at 400-800, phenols, and alcoholic groups at 1,000-1,400, carboxyl group at 1,500-1,700 cm -1 , hydroxyl group: 3,200-3,400 cm -1 .…”
Section: Ftir and Sem Analysis Of Scenedesmus Spmentioning
confidence: 94%
“…Currently, the use of liquid digestate as a substrate for microalgae growth medium has attracted much attention as a wastewater treatment technology with the simultaneous sustainable microalgae biomass feedstock production [10][11][12][13]. Microalgae have the ability to efficiently utilize nutrients from liquid fraction of digestate, and mixotrophic cultivation may enhance inorganic and organic carbon removal, while providing biomass for bioenergy applications [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a need for overcoming the limitations to upgrade algal fuel production from pilot to commercial level. A major challenge for the effective microalgae production is the liquid digestate treatment to control the high turbidity of digestate, high and unbalanced nutrients concentrations, content of competing microorganisms, and the potential toxicity caused by organic compounds and ammonia concentrations [7,10,15].…”
Section: Introductionmentioning
confidence: 99%
“…In theory, one Chlorella cell can reproduce 100 million cells within 10 days, nearly equally to the speed of nuclear fission (2). Besides, C. pyrenoidosa is increasingly used for industrial and biomedical applications, such as CO2 flue gas fixation (3,4), biodiesel production (5,6), high-value nutritional extracts (7)(8)(9)(10), and anti-inflammatory products (1, 11). Moreover, nuclear radiation (12)(13)(14) is commonly used in full-scale bioreactors (15) to realize specified functions, such as increasing removal of pollutants from wastewater (16), higher CO2 concentration fixation (17), and increased biodiesel production (18).…”
Section: Introductionmentioning
confidence: 99%